The Influences of Brand Awareness on Consumers’ Cognitive Process: An Event-Related Potentials Study - Zhang, Xuefeng (Frontiers in Neuroscience, 2020)
Brand awareness plays an important role in most aspects of marketing. However, consumers’ cognitive process of brand awareness, which plays an important role in purchase decision or product usage experiences, is still unclear in the brain. Using event-related potentials (ERPs), the influences of two different brand awareness on consumers’ cognitive process was investigated. Phone pictures with high or low brand awareness and girl pictures were used to carry out this experiment research. An amended oddball task was designed in which girl photos were taken as target stimuli, and phone pictures were taken as non-target stimuli. Subjects were asked to identify the girl pictures. Smaller ERPs components N2 and P3 along with high brand awareness phone pictures were found compared to the low brand awareness ones. The amplitude variation in N2 and P3 indicated that the cognitive process of identification and attention distribution were changed along with the magnitude of brand awareness, which meant consumer could allocate different attention resources to distinguish high or low brand awareness product unconsciously. This may indicate the identification and attention distribution caused by brand awareness can be detected by N2 and P3, and event-related potentials methodology may be a sensitive measurement technique for brand awareness.